2007
DOI: 10.1128/jb.00685-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofAeromonas veroniiGenes Required for Colonization of the Medicinal Leech,Hirudo verbana

Abstract: Most digestive tracts contain a complex consortium of beneficial microorganisms, making it challenging to tease apart the molecular interactions between symbiont and host. The digestive tract of Hirudo verbana, the medicinal leech, is an ideal model system because it harbors a simple microbial community in the crop, comprising the genetically amenable Aeromonas veronii and a Rikenella-like bacterium. Signature-tagged mutagenesis (STM) was used to identify genes required for digestive tract colonization. Of 3,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 71 publications
3
65
0
1
Order By: Relevance
“…A total of 5,088 transposon mutants of WT CO92 were created, which included 96 mutants for each of the 53 unique 40-bp signature tags (34). As a source of the tags, 53 E. coli S-17 strains, each harboring the plasmid pUTminiTn5Km2STM with a unique tag, were used as donor strains and conjugated with WT CO92 (35). Initially, 56 tags were chosen, as previously described (35), and were tested for their cross-hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 5,088 transposon mutants of WT CO92 were created, which included 96 mutants for each of the 53 unique 40-bp signature tags (34). As a source of the tags, 53 E. coli S-17 strains, each harboring the plasmid pUTminiTn5Km2STM with a unique tag, were used as donor strains and conjugated with WT CO92 (35). Initially, 56 tags were chosen, as previously described (35), and were tested for their cross-hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…streptomycin versus rifampicin), and the corresponding bacterial loads were then determined. The competitive index (CI) was calculated as follows: CI5(mutant output/WT output)/(mutant input/WT input) (Silver et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…on May 10, 2018 by guest http://cmr.asm.org/ presently unknown (266). Such a model offers exciting opportunities to potentially discover important genes and gene products critical to colonization of digestive tracts in susceptible hosts.…”
Section: Animal Models Of Infectionmentioning
confidence: 99%
“…The microbiota of the leech's crop is normally populated by only two resident symbiotic microbial species, one of which (Aeromonas) can be grown in vitro and is amenable to genetic manipulation. Silver et al (266) have identified several classes of genes that play important roles in colonization of the leech digestive tract, including bacterial cell surface modifications, regulatory factors, nutritional elements (amino acid and phosphate transporters), and genes involved in type three secretion systems (TTSS). Mutants in specific genes, such as that encoding Braun's major outer membrane lipoprotein or a gene encoding a cytoplasmic membrane component of a TTSS, compete 10,000-to 25,000-fold less efficiently against wild-type or competitor strains in colonization of the leech's crop (265,266).…”
Section: Animal Models Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation